"20, 000 leagues under the sea": Sleep, cognitive performance, and self-reported recovery status during a 67-day military submarine mission. (February 2021) - Nieuwenhuys, Arne; Dora, Jonas; Knufinke-Meyfroyt, Melanie; Beckers, Debby; Rietjens, Gerard; Helmhout, Pieter
Abstract: Employing a field-based monitoring paradigm, the current study examined day-to-day fluctuations in actigraphy-based sleep recordings, cognitive performance (10-min psychomotor vigilance test; PVT), and self-reported recovery status among 14 submariners throughout a 67-day military mission. Mission averages reflected suboptimal sleep that was of short overall duration (5:46 ± 1:29 h per 24-h day) and relatively low efficiency (82.5 ± 9.9%); suboptimal levels of cognitive performance (PVT mRT = 283 ± 35 ms; PVT response errors = 5.3 ± 4.8); and moderate levels of self-reported recovery. Whilst self-reported recovery status remained stable across mission days, small but consistent day-to-day increases in sleep onset latency and PVT mRT accumulated to reflect meaningful deterioration in sleep and cognitive performance across the entire 67-day mission (i.e., 47% and 16% of the overall mission average, respectively). Future work is required to corroborate the current findings, firmly establish underlying causes, and make evidence-based suggestions for interventions to improve and uphold submariners' health and performance. Highlights: Sleep during a 67-day submarine mission is fragmented and of short duration. Mission averages reflect sub-optimal levels of cognitive performance. Self-perceived recovery status (vigor, affect, rumination) was moderate at best. Sleep onset latencies and PVT reaction times deteriorated on a 'day-to-day' basis. Across the entire mission, observed declines reached clinically significant levels.